QUO VADIS THE LEGAL POLITICS OF FILLING CONSTITUTIONAL JUDGE POSITIONS IN INDONESIA - Rizkiya Muhlas, Nur; Ali Safa’at , Muchamad; Dwi Qurbani , Indah (IBLAM LAW REVIEW, 2023)
The unconstitutional dismissal of Aswanto as a constitutional judge by the DPR has faced much opposition from legal scholars. The actions of the DPR stem from its inherent authority as an institution that can propose three constitutional judges. Therefore, the DPR believes that as a proposing institution, it can oversee and dismiss constitutional judges during their term, which is not part of its authority. The mechanism of selecting constitutional judges with the three-branch model of government has caused problems and confusion in the constitutional law. This article will focus on discussing the Quo Vadis of the legal politics of filling the position of constitutional judges, which comes from the three branches of government and the reconstruction of the mechanism for filling the position of constitutional judges in the future. This research has produced several discussion points, including: (1) the legal politics of filling the position of constitutional judges by the three branches of judicial power, which is a reflection of the checks and balances, has been misused by the DPR as an instrument to weaken the body of the Constitutional Court, especially the independence of constitutional judges. (2) The reconstruction of the institution proposing constitutional judges can be carried out by the Judicial Commission by aligning the proposing institutions of the Supreme Court and the Constitutional Court.